The Character of Dual Site Adsorbent on Coal Fly Ash Toward Benzene Adsorption - Astuti, Widi; Wahyuni, Endang Tri; Prasetya, Agus; Bendiyasa, I Made (European Journal of Sustainable Development, 2014)
Large quantities of coal fly ash (CFA) are produced during combustion of coal in the production of electricity. Most of this ash has not been widely used. CFA is mainly composed of some oxides including Al2O3 and SiO2 having active site and unburned carbon as a mesopore that enables it to act as a dual site adsorbent. To get different characters of dual site, CFA was sieved using 150 mesh size, heated at 400oC and reacted with sodium hydroxide solution. Furthermore, CFA was used as adsorbent of benzene in aqueous solutions. Equilibrium data were evaluated by single site and dual site isotherm models. It can be concluded that single site model yielded excellent fit with equilibrium data of benzene. The values of maximum concentration of adsorbate in solid surface (C?m) and Langmuir constant (KL) are affected by [Si+Al]/C ratio in CFA. The increase of [Si+Al]/C ratio causes a decrease of qm and KL values. Keywords : coal fly ash, adsorption, benzene